PENDIDIKAN KARAKTER MELALUI PELAJARAN PAI (PENDEKATAN KURIKULUM 2013) - Nurmin, Nurmin (Jurnal Pendidikan Guru, 2017)
Education as a vital part in creating a civilized man then Islam as the perfect religion which Allah has given the concept of living according denagn human nature. Both in creating perberadaban, or in pendidika. Then the position of Islamic education is as funnel setrategis in voicing the prophetic ideals (prophetic) in the enforcement of the human civilization and morals. While the condition of Islam ravaged in recent years, with the cultural divide in society, especially among the younger generation, that the development orientation of the material far beyond the speed of spiritual, moral, and social. due to cultural gaps that occur also experienced a loss of public civilization, culture and religion becomes drier as it has shades of power, so that religion is now more of a contestation and lost his spirit. So to respond to the problems the author tries to give a solution bid to restore menyudahinya through moral education through PAI lesson, heres a big goal of this paper. That the Islamic Religious Education (PAI) is one of the pillars of character education is the most important. Character education will grow well if starting from the religious soul embedded in children, therefore the material PAI school became one of the supporting character education. Through pembelajaaran PAI students are taught aqidah as the basis of religious, taught the Koran and the Hadith as a guide to life, taught jurisprudence as safeguards established in worship, teaching the history of Islam as a keteladan life, and teach morals to guide human behavior whether in either category or bad. Therefore, the main purpose of the Learning PAI is the formation of the personality of the student are reflected in behavior and thought patterns in everyday life. In addition, successful learning in school PAI one of which is also determined by the application of appropriate learning methods.